DECENT COMPENSATION SUPPORTS MOTIVATION EMPLOYEE WORK: Study at PT. WANGTA AGUNG in Surabaya - Winarni, Roro Suestu Diyah (International Journal of Multidisciplinary Research and Literature, 2022)
The human resource factor plays an important role in a company and has an important meaning in achieving the company's goals, because no matter how advanced the equipment used by the company is without the human element running it, the equipment will not function properly. Such is the importance of employees for the company. According to the company to give good attention to its employees, for example, giving proper compensation. Decent rewards received by employees are expected to meet the needs of employees personally and socially, so that employees get satisfaction in doing their jobs so that when they work they can work well, be more serious and have high work motivation. This studies become performed with the intention of knowing the impact of compensation on employee motivation at PT. Wangta Agung Shoe Production Division. While the purpose of this research is to find out how the implementation of compensation provided by PT. Wangta Agung to his employees. To find out a description of the work motivation of employees at PT. Great Wang. To find out how compensation can provide work motivation to the work of employees at PT. Great Wang. Improving employee work, the company should pay more attention to the policy of providing wages (compensation) to employees considering that the provision of wages is an incentive for employees to be more concentrated and more active in work (motivating). The existing compensation system is already considered good by employees. Currently the company only needs to maintain the system that has been running well. If it is deemed possible, increasing employee wages seems to be a good way to increase employee morale. With increasing employee work, it will encourage an increase in the number of company production well